Characterization of agrobacterium tumefaciens Strains isolated from root nodules of vigna Trilobata (l) verdc. Cultivars. - G. KRANTHI KUMAR,; M. RAGHU RAM, (International Journal of Pharma and Bio Sciences, 2016)
Root nodulating bacteria was isolated from root nodules of Vigna trilobata (L) Verdc. Plants raised in the soils were collected from five geographically different areas in Andhra Pradesh, India. The bacteria was identified as Agrobacterium tumefaciens strains by 16S rDNA analysis. Except A. tumefaciens MRR 102, all the strains produced round shape and white coloured colonies with lot of mucilage on YEMA medium. All the Agrobacterium strains grew well on YEM medium with NaCl (0.1%), pH (7.0), and at temperature 35â°C. All the five strains were positive for biochemical tests such as Ammonia production test, catalase test, oxidase test, nitrate reduction test, and urease test. All these strains showed negative results on Hoffer’s Alkaline medium, Ketolactose test, and Glucose peptone Agar medium. A. tumefaciens MRR 102 showed the negative results on amylase test and the remaining isolates showed positive. For citrate utilization except A. tumefaciens MRR 115, all the strains showed the positive results. Plant growth promoting characteristics such as Phosphate solubilization, IAA, EPS chitinase, siderophore and HCN production were estimated for these Agrobacterium strains. IAA and EPS production was observed in all these strains with a range of 30-120 µg/ml and 402-569 mg/ml respectively. Two out of five strains i.e. A. tumefaciens MRR 102 and A. tumefaciens MRR 105 showed the phosphate solubilization. Only one strain A. tumefaciens MRR 111 showed the chitinase production (0.20 U/ml) on chitin agar medium. Two out of five Agrobacterium sp. namely MRR 102 and 105 showed the Siderophore production. The two strains A. tumefaciens MRR 108 and A. tumefaciens MRR 111 showed the positive results for HCN production. Among the five strains, A. tumefaciens MRR 111 and A. tumefaciens MRR 102 strains was found to most effective in positively enhancing the growth and the plant growth promoting characteristics in all parameters.